Hidden narratives of transnational organised crime in West Africa, 2022 - Klantschnig, Gernot (UK Data Service, 2023)
The foundation of the project was ethically rigorous fieldwork on insider narratives of activities labelled transnational organised crime (TNOC). This was done through in-depth interviews with difficult to access market insiders and regulators in the illicit migrant transport economy in Agadez and the illicit opioid economy in Lagos. We shared/archived the core of this interview data in the form of redacted interview transcripts. Due to geographical focus of the research, the archived transcripts are in three different languages (English, Nigerian Pidgin and French). This project investigated the understandings of activities labelled transnational organised crime (TNOC) in West Africa. The project assumed that the ways illicit and state actors speak about and understand their roles, i.e. their 'narratives', provides a helpful entry point into a better understanding of the everyday reality of participating in and seeking to counter criminalised activities. The project was built on the observation that much of our understanding of TNOC in West Africa is based on official reports, statistics and other largely detached assessments. Using the cases of the illicit opioid trade and the illicit transport of migrants, the project sought to uncover the 'hidden narratives' of these activities in West Africa.